From 'Foreign Natives' to 'Native Foreigners'. Explaining Xenophobia in Post-apartheid South Africa : Explaining Xenophobia in Post-apartheid South Africa - Neocosmos, M. (Book collections on Project MUSE., 2006)
Xenophobia is a political discourse. As such, its historical development as well as the conditions of its existence must be elucidated in terms of the practices and prescriptions that structure the field of politics. In South Africa, its history is connected to the manner citizenship has been conceived and fought over during the past fifty years at least. Migrant labour was de-nationalised by the apartheid state, while African nationalism saw it as the very foundation of that oppressive system. However, only those who could show a family connection with the colonial/apartheid formation of South Africa could claim citizenship at liberation. Others were excluded and seen as unjustified claimants to national resources. Xenophobia's current conditions of existence are to be found in the politics of a post-apartheid nationalism were state prescriptions founded on indigeneity have been allowed to dominate uncontested in condition of passive citizenship. The de-politicisation of a population, which had been able to assert its agency during the 1980s, through a discourse of 'human rights' in particular, has contributed to this passivity. State liberal politics have remained largely unchallenged. As in other cases of post-colonial transition in Africa, the hegemony of xenophobic discourse, the book shows, is to be sought in the character of the state consensus. Only a rethinking of citizenship as an active political identity can re-institute political agency and hence begin to provide alternative prescriptions to the political consensus of state-induced exclusion.